An Assessment of School Leaders' Management of Finances and Resources: Basis for Development Program - Santos, Orlando R.; Caparas, Laurene Anne R.; Roquero, Lorie B.; Diesta, Rachelle; Eligue, Liezel A.; de Jesus, Aileen P.; Rosario, Elvie B. Del; Orito, Melchy O.; Ventura, Maria Elena R.; Cabigao, John Paul E.; Paz, Rosalia M.; Ampo, Patrick Hamilcar Barriga (Future Science / FSH-PH Publications, 2021)
This study aimed to assess school leaders’ management of financial and resources in public elementary schools in District 18, Schools Division of Rizal, DepEd Region IV-A. This research study used descriptive-survey as the study’s research design. The respondents of the study comprised of teachers and school leaders. Findings of the study revealed that that majority are female, married, master’s degree holder, had an academic rank of Teacher I to Teacher III for teachers and appointed permanent principal for school leaders and in the service for more than 11 years. School Leaders’ Performance in Management of Finances and Resources in term of regular resource inventory was advance, while, regular dialogue for planning and resource programming and community-developed resource management system were developing. There is no significant difference on the assessment of school leaders’ management of financial and resources when grouped into school leaders and teachers. However, the researchers can infer that there is a significant difference on the scores of respondents on approved school operating budget and school inventory of resources. There is no significant difference on the assessment of school leaders’ management of financial and resources when compared into research survey results and SBM assessment of Region IV-A CALABARZON, Schools Division of Rizal. This study recommends an excellent financial plan that teachers and school heads collaborated in drafting it. This may plan according the management of finances and resources of the school